2015
DOI: 10.1016/j.apenergy.2015.08.131
|View full text |Cite
|
Sign up to set email alerts
|

Vapor pressure and corrosivity of ternary metal-chloride molten-salt based heat transfer fluids for use in concentrating solar power systems

Abstract: h i g h l i g h t sApplicability of NaCl-KCl-ZnCl 2 salts for CSP applications is evaluated. Corrosion rates are estimated by electrochemical and immersion methods. Hastelloys show corrosion rates of <10 lm/year at 800°C under anaerobic conditions. g r a p h i c a l a b s t r a c t a b s t r a c t Higher operating temperatures increase efficiency of the concentrating solar power plants but promote faster corrosion of the pipes and vessels made of Hastelloy or stainless steel materials for the moltensalt mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(73 citation statements)
references
References 26 publications
3
70
0
Order By: Relevance
“…A recent literature review concluded that purified salts and sealed containers had a significant effect on corrosion rates . Also, in the recent chloride salt literature, it is common to extrapolate isothermal results and report an annualized rate of attack (i.e., µm/yr) as a performance metric . That is inappropriate for two main reasons: first, an assumption must be made about the kinetics and the assumption of a linear extrapolation is not based on any mechanistic understanding or data.…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review concluded that purified salts and sealed containers had a significant effect on corrosion rates . Also, in the recent chloride salt literature, it is common to extrapolate isothermal results and report an annualized rate of attack (i.e., µm/yr) as a performance metric . That is inappropriate for two main reasons: first, an assumption must be made about the kinetics and the assumption of a linear extrapolation is not based on any mechanistic understanding or data.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, numerous studies have explored the corrosion behaviour of potential construction materials with different storage media or heat transfer fluids. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Molten nitrate salt, known as Solar Salt, is the most technologically mature solution for CSP. It consists of 60 wt% NaNO 3 -40 wt%KNO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The ternary salt Li 2 CO 3 -Na 2 CO 3 -K 2 CO 3 was investigated for compatibility with HR3C steel (25%Cr-20%Ni-53%Fe), demonstrating that oxidation is the main corrosion mechanism. 21 Hastelloy C-276 and C-22 and stainless steel 304 with chloride salts were studied at temperatures up to 900°C in the presence 22,23 and absence 23 of air. The authors concluded that the corrosion rates decrease with the absence of oxygen in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Immersion method was most widely used by researchers to describe the corrosion behaviors of alloys in the molten salt mixtures . Vignarooban et al have studied the corrosion behaviors for Hastelloys and stainless steels in ternary molten salt system, calculated the corrosion rates for different alloys with and without air and ranked the corrosion resistance of each alloy for potential applications. Fernandez et al have studied corrosion products and corrosion layer formed in a ternary nitrate/nitrite molten salt system for alloys such as 122 steels.…”
Section: Introductionmentioning
confidence: 99%